Persistently short or long sleep duration increases the risk of sensory impairment in Chinese older adults - Yang, Ling; Du, Jing; Duan, Ying; Cui, Yan; Qi, Qi; Liu, Zihao; Liu, Huaqing (Frontiers in Public Health, 2024)
Background Cross-sectional evidence suggests that persistently short or long sleep duration is associated with sensory impairment. Thus, this study was conducted to investigate the associations between sleep duration and altered sleep duration with sensory impairment in Chinese older adults. Methods Longitudinal data (2008–2014) obtained through the Chinese Longitudinal Healthy Longevity Survey (CLHLS) were analyzed. Sleep duration was classified as normal (7–8 h), short (<7 h), or long (≥9 h). Sensory impairment was assessed using individuals’ self-reported data on visual and hearing functions. Cox regression was performed to evaluate the effects of sleep duration and altered sleep duration on sensory impairment, including visual impairment (VI) and hearing impairment (HI). Results This study included 3,578 older adults (mean age: 78.12 ± 9.59 years). Among them, 2,690 (75.2%) were aged 65–84 years and 1798 (50.3%) were women. The risks of VI (hazard ratio [HR]: 1.14; 95% confidence interval [CI]: 1.02–1.29), HI (HR: 1.14; 95% CI: 1.00–1.30), and dual sensory impairment (both VI and HI; HR: 1.26; 95% CI: 1.03–1.55) were high in older adults with long sleep duration. In addition, the risks of VI, HI, and dual sensory impairment were high in individuals whose sleep duration changed from normal to short or long (HR: 1.20 [95% CI: 1.02–1.42], 1.26 [95% CI: 1.03–1.53], and 1.54 [95% CI: 1.11–2.12], respectively) and those with persistently short or long sleep duration (HR: 1.25 [95% CI: 1.07–1.46], 1.34 [95% CI: 1.11–1.61], and 1.67 [95% CI: 1.22–2.27], respectively). Conclusion A prospective association was identified between altered sleep duration and sensory impairment in Chinese older adults. Our findings highlight the importance of optimal sleep duration and healthy sleep habits in preventing sensory impairment in older adults.